The Meaning of Critical Pedagogy (after Freire) for Teaching Philosophy - Štempihar, Marko (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
In our article, we tackle some of the ideas of critical pedagogy after Freire and their meaning for the didactics of philosophy. At the beginning, we demonstrate how Freire's understanding of the dialogical method is placed in his critique of pedagogical practices. With the concept of dialogue, Freire proposes a new approach, the one that would correspond to his idea of pedagogy of freedom. In continuation, we analyse Freire’s concept of dialogue and we show how it is related to the dialogical method of teaching philosophy, especially in relation to the Socratic method. We illustrate theoretical concepts with examples from our teaching practice. We conclude that critical pedagogy is important for philosophical didactics, since it provides us with tools for understanding how each teaching practice is embedded in a social environment that is also a political space. Such reflection can then help us with a better realization of the pedagogical goals of our teaching subject.